Infant nutrition in the first seven days of life in rural northern Ghana - Aborigo Raymond; Moyer Cheryl A; Rominski Sarah; Adongo Philip; Williams John; Logonia Gideon; Affah Gideon; Hodgson Abraham; Engmann Cyril (BMC Pregnancy and Childbirth, 2012)
Abstract Background Good nutrition is essential for increasing survival rates of infants. This study explored infant feeding practices in a resource-poor setting and assessed implications for future interventions focused on improving newborn health. Methods The study took place in the Kassena-Nankana District of the Upper East Region of northern Ghana. In-depth interviews were conducted with 35 women with newborn infants, 8 traditional birth attendants and local healers, and 16 community leaders. An additional 18 focus group discussions were conducted with household heads, compound heads and grandmothers. All interviews and discussions were audio taped, transcribed verbatim and analyzed using NVivo 9.0. Results Community members are knowledgeable about the importance of breastfeeding, and most women with newborn infants do attempt to breastfeed. However, data suggest that traditional practices related to breastfeeding and infant nutrition continue, despite knowledge of clinical guidelines. Such traditional practices include feeding newborn infants water, gripe water, local herbs, or traditionally meaningful foods such as water mixed with the flour of guinea corn (yara’na). In this region in Ghana, there are significant cultural traditions associated with breastfeeding. For example, colostrum from first-time mothers is often tested for bitterness by putting ants in it – a process that leads to a delay in initiating breastfeeding. Our data also indicate that grandmothers – typically the mother-in-laws – wield enormous power in these communities, and their desires significantly influence breastfeeding initiation, exclusivity, and maintenance. Conclusion Prelacteal feeding is still common in rural Ghana despite demonstrating high knowledge of appropriate feeding practices. Future interventions that focus on grandmothers and religious leaders are likely to prove valuable in changing community attitudes, beliefs, and practices with regard to infant nutrition.